0429 Daytime workplace noise exposures lower than occupational criteria can disturb nighttime sleep. (21st August 2017) - Guo, Leon; Lin, Cheng-Yu; Tsai, Perng-Jy; Lin, Kuei-Yi; Chen, Chih-Yong; Chung, Lin-Hui; Wu, Jiunn-Liang
Abstract : Background: Nighttime noise exposure has been shown to affect sleep quality. However, effects of daytime noise exposure on nighttime sleep have been inconclusive. A quasi-experimental study was carried out using crossover design to determine daytime occupational noise exposure on polysomnography (PSG)-documented sleep quality. Methods: From two hospital cafeterias, 48 employees were recruited to participate in this study. Each participant was randomly assigned to expose to high noise level areas for 8 hours and, on a separate occasion, low noise level areas for 8 hours. The high and low noise periods were separated by a washout period of 14 days. Personal noise exposure, pure tone audiometry, autonomic nerve system (ANS) function tests, and over-night PSG were measured. Results: A total of 20 men and 20 women completed the study, with average tenure of 10.0 years. Average daily noise exposure (time-weighted average in 8 hours, TWA-8 hours) was 73.5 dBA during the high noise exposure day, and 64.4 dBA during the lower noise day (p=0.001). Subjective sleep quality was not different between nights after higher and lower noise days. Comparing to nights after low noise days, deep sleep by PSG was significantly shorter, sleep efficiency worse, resting heart beats and blood pressure after cold pressor test (CPT) higher after high noise days, after adjusting for covariates. Conclusions: Daytime noise exposure had a sustained effect on nighttime sleep, including shorter deep sleep and lower sleep efficiency. The sleep disturbance could be partially explained by post-shift ANS activity.